MEASUREMENT OF PHYSIOGRAPHIC CHANGES ON MANGROVE-FRINGED ESTUARIES AND COASTLINES - Bird, E. C.F.; Barson, M. M. (Marine Research in Indonesia, 1977)
Studies of physiographic changes are in progress on mangrove-fringed shorelines in Westernport Bay in Victoria, and Cairns Bay in Queensland, Australia. Historical evidence of advance or retreat of these shorelines has been obtained from comparison of historical maps and air photographs with the present configuration, and supplemented by monitoring shoreline" changes with reference to established datum points during the past decade. In addition, changes in substrate level within the mangrove fringe, on mudflats to seaward, and on salt marshes (where present) to landward have been measured with reference to vertical changes on inserted poles, accretion over emplaced brick-dust layers, and changes in probe depths to underlying horizons (rock, sand, or peat) Results indicate that the advance of Avicennia marina on to mudflats is followed by relatively rapid and generally sustained vertical accretion related to interception of sediment within pneumatophore fields. Other mangroves or salt marsh species then replace Avicennia, and continued accretion leads to the development of a depositional marshland terrace, representing a re-shaping of the inter-tidal profile by the agency of vegetation. Mangroves that produce pneumatophore fields are considered to be more effective in trapping sediments than stilt rooted mangroves such as Rhizophora spp. or buttressed mangroves such as Bruguiera spp.